Catalytic Methane Decomposition over Fe‐Al2O3. Issue 11 (9th May 2016) - Zhou, Lu; Enakonda, Linga Reddy; Saih, Youssef; Loptain, Sergei; Gary, Daniel; Del‐Gallo, Pascal; Basset, Jean‐Marie
Abstract: The presence of a Fe–FeAl2 O4 structure over an Fe–Al2 O3 catalysts is demonstrated to be vital for the catalytic methane decomposition (CMD) activity. After H2 reduction at 750 °C, Fe–Al2 O3 prepared by means of a fusion method, containing 86.5 wt % FeAl2 O4 and 13.5 wt % Fe 0, showed a stable CMD activity at 750 °C for as long as 10 h. Abstract : Ironing methane composition : For the first time, the presence of the Fe–FeAl2 O4 structure over Fe–Al2 O3 catalysts is demonstrated to be vital for the catalytic methane decomposition (CMD) activity. After H2 reduction at 750 °C, the Fe–Al2 O3 sample prepared by a fusion method contains a high amount of FeAl2 O4 and only little Fe 0 and shows a stable CMD activity at 750 °C for as long as 10 h.